Podstawowe problemy reformy służby cywilnej w nowym ustroju społeczno-gospodarczym: [Basic problems related to Civil Service law reforms in new social and economic system] (Studia Prawnicze / The Legal Studies, 2007)
Zgodnie z tradycyjną koncepcją prawa urzędniczego praca w aparacie publicznym była służbą publiczną pełnioną przez jednostkę, której osobiste interesy podporządkowano naczelnym interesom państwa. Między państwem a urzędnikami istniały stosunki o charakterze administracyjnoprawnym, oparte na hierarchii służbowej, której towarzyszyła daleko posunięta dyspozycyjność urzędnika piastującego swój urząd na podstawie mianowania. W zamian za wierną służbę i posłuszeństwo urzędnik korzystał ze specjalnych przywilejów w postaci wysokiego uposażenia, stabilizacji zatrudnienia oraz odrębnego, korzystniejszego niż powszechne, zaopatrzenia emerytalnego1. Do założeń biurokratycznego modelu służby publicznej nawiązywała ustawa z 17 lutego 1922 r. o państwowej służbie cywilnej oraz ustawa śląska z 22 czerwca 1934 r. o stosunkach służbowych śląskich funkcjonarjuszów wojewódzkich.  The critical issue for proper functioning of civil services in Poland is proper normalization of legał status of civil servants, notably those assigned to managerial positions and other independent positions related to performance of tasks for the State, by issuing decisions, their procurement or execution.Civil Service Act dated 24 August 2006 has however some shortcomings. Among most serious are: too narrow itemized scope of Act, no implementation of eąual acess to Civil Service principle, which affects the transparency of recruitment to Civil Service and competition status of CS ąualification procedurę. Some other regulations, conceming remunerations, working time in Civil Service, and some Solutions of collective employment law, are to be altered.Based on discussions the thesis can be put forward that deeper amendment to Civil Service Act, as well as other regulations, is reąuired to normalize indicidual elements goveming civil servants’ legał status, one compliant with intemational law.